Interaction of Helicobacter pylori with C-Type Lectin Dendritic Cell-Specific ICAM Grabbing Nonintegrin. (5th April 2012) - Miszczyk, Eliza; Rudnicka, Karolina; Moran, Anthony P.; Fol, Marek; Kowalewicz-Kulbat, Magdalena; Druszczyńska, Magdalena; Matusiak, Agnieszka; Walencka, Maria; Rudnicka, Wiesława; Chmiela, Magdalena
Abstract : In this study we asked whether Helicobacter pylori whole cells and lipopolysaccharide (LPS) utilize sugar moieties of Lewis (Le) antigenic determinants to interact with DC-SIGN (dendritic cell specific ICAM grabbing nonintegrin) receptor on dendritic cells (DCs). For this purpose the soluble DC-SIGN/Fc adhesion assay and the THP-1 leukemia cells with induced expression of DC-SIGN were used. We showed that the binding specificity of DC-SIGN with H. pylori Le X/Y positive whole cells and H. pylori LPS of Le X/Y type was fucose dependent, whereas in Le XY negative H. pylori strains and LPS preparations without Lewis determinants, this binding was galactose dependent. The binding of soluble synthetic Le X and Le Y to the DC-SIGN-like receptor on THP-1 cells was also observed. In conclusion, the Le XY dependent as well as independent binding of H. pylori whole cells and H. pylori LPS to DC-SIGN was described. Moreover, we demonstrated that THP-1 cells may serve as an in vitro model for the assessment of H. pylori -DC-SIGN interactions mediated by Le X and Le Y determinants.